PENYUSUNAN INDEX OF REGIONAL EDUCATION ADVANTAGE (IREA) UNTUK ANALISIS KETIMPANGAN PENDIDIKAN DI INDONESIA DENGAN PENDEKATAN KAPABILITAS PENDIDIKAN - Yoga Dwi Nugroho; Dita Desriani (ITB AAS INDONESIA Surakarta, 2022)
The demographic dividend is a strategic opportunity for Indonesia to accelerate economic development, with the availability of human resources by productive age in significant numbers. However, the low quality of existing education makes the demographic dividend cannot be reaped optimally. One of the reasons for this indication is the high inequality in education, which reflects the quality of human resources. Besides, one of the indicators for analyzing educational inequality is the Index of Regional Education Advantage (IERA), which comprehensively analyzes educational inequality through Amartya Sen's capability approach. The dimensions used comprise enrolment, attainment, and provision. In this regard, the province with the highest IREA score is DKI Jakarta, whereas the province with the lowest IREA score is Papua. The high IREA score means the better the quality of education, the better the results of achieving basic education indicators, and the stronger the human resources. The study results revealed a fairly high educational disparity between the western and eastern regions of Indonesia, which was analyzed from the distribution of the IREA value of each province. Demographic dividend, inequality of education, IREA, enrolment, attainment, provision